Analisis Pengembangan Organisasi Pelayanan Publik melalui Proses Diagnosa dan Intervensi - Hardiyansyah, Hardiyansyah; Sumantri, A.; Zaitun, Aspi; Mellita, Dina; Mukran, Mukran (Jurnal Ilmiah Administrasi Publik, 2019)
The purpose attempts to find out an analyze the factors that become obstacles in tax services through the process of diagnosis, intervention and organizational development by looking at and reviewing organizational goals, organizational structure, relationships, rewards, leadership and organizational work mechanism KPP Pratama Palembang Ilir Timur. The method used is quantitative descriptive with the Weisbord model through the distribution of questionnaires to respondents from the state civil apparatus (ASN) as much as 16 percent of the 126 population, namely 20 respondents. The results of the study and discussion concluded that all variables in the diagnostic process had proceeded well according to the facts and data obtained. The facts and data indicate that KPP Pratama Palembang Ilir Timuris not problematic and that in the present conditions it is not necessary to intervene in the development of Palembang Ilir Timur Primary Tax Office.